Rare case of two siblings with complete androgen insensitivity syndrome - Shankar, Ambika; Nagar, Oby; Saini, Suwaram; ., Babita (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Androgen insensitivity syndrome (AIS) also called testicular feminizing syndrome is a rare X linked disorder of sexual differentiation caused by mutation in the androgen receptor (AR) gene, which is located on the X chromosome (Xq11-q12). In the reported cases, individuals with complete androgen insensitivity syndrome (CAIS) presented with a female appearance and normal breast development, absence of uterus and ovaries, bilateral undescended testis, and elevated testosterone levels. The syndrome is usually detected on evaluation of a phenotypic female with primary amenorrhea who presents for treatment of infertility. Here, we report 2 cases of CAIS in siblings 21 and 19 years of age who presented to us with primary amenorrhea. The elder sibling presented to us with primary amenorrhea, thelarche +, absent adrenarche, blind pouch of vagina, b/l inguinal masses suggestive of undescended testes, raised serum testosterone and absent uterus on USG. While the younger sibling also presented with similar findings but had history of b/l orchidectomy at the age of 14 years. Both the sisters were admitted in our unit and the elder sister underwent b/l orchidectomy and McIndoe’s vaginoplasty. While the younger sister underwent McIndoe’s vaginoplasty on the same day. Post-operative recovery was uneventful and they were given hormone replacement therapy (HRT). AIS is a rare X linked disease caused by mutation in the AR gene. which when diagnosed early can be treated appropriately. Precise diagnosis requires clinical, hormonal and molecular investigation and is of great importance for appropriate gender assignment and management in general. With timely gonadectomy, vaginoplasty or vaginal pouch deepening, hormone replacement and appropriate psychological support help the person live a healthy and almost normal life.